An Unmanned Aerial Vehicles Journey into the World of Sugarcane - Barbosa Júnior, Marcelo Rodrigues [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
In this PhD Dissertation we investigated the use of unmanned aerial vehicles (UAVs) in sugarcane production, emphasizing their increasing importance in agriculture and the strategic role of sugarcane. The research includes an integrative review of UAV applications from 2016 to 2021, analyzing monitoring and management strategies and assessing the contributions of various countries and institutions. Consequently, we present a new protocol to determine ideal UAV flight times to discriminate sugarcane cultivars during early stage of development using multispectral images and vegetation indices. Furthermore, we used machine learning (ML) algorithms combined with UAV imagery to predict sugar content in sugarcane, offering a superior, non-invasive, and scalable method compared to traditional techniques. This approach was also enhanced with the incorporation of a proximal active sensor, improving the prediction capabilities for bioethanol feedstocks and promoting sustainable land use by considering all plant components as valuable resources. The final chapter summarizes the progress of UAV technology applications in sugarcane, discusses the utility and transferability of the methods developed, and describes future research directions to further advance in this field. Finally, this PhD Dissertation offers significant insight into optimizing sugarcane production through the integration of innovative technologies.

Nesta Tese de Doutorado investigamos o uso de veículos aéreos não tripulados (VANTs) na produção de cana-de-açúcar, enfatizando sua crescente importância na agricultura e o papel estratégico da cana-de-açúcar. A pesquisa inclui uma revisão integrativa das aplicações de VANTs de 2016 a 2021, analisando as estratégias de monitoramento e gerenciamento e avaliando as contribuições de diversos países e instituições. Consequentemente, apresentamos um novo protocolo para determinar horários ideais de voo de VANT para discriminar cultivares de cana-de-açúcar durante estádio inicial de desenvolvimento das plantas usando imagens multiespectrais e índices de vegetação. Além disso, usamos algoritmos de machine learning (ML) combinados com imagens de VANT para prever o teor de açúcar da cana-de-açúcar, oferecendo um método não invasivo e escalável superior às técnicas tradicionais. Essa abordagem também foi ampliada com a incorporação de um sensor ativo proximal, melhorando os recursos de predição para matérias-primas de bioetanol e promovendo o uso sustentável da terra ao considerar todos os componentes da planta como recursos valiosos. O capítulo final resume o progresso das aplicações da tecnologia de VANT na cana-de-açúcar, discute a utilidade e a capacidade de transferência dos métodos desenvolvidos e descreve as futuras direções de pesquisa para avançar ainda mais nesse campo. Por fim, esta Tese de Doutorado oferece uma visão significativa da otimização da produção de cana-de-açúcar por meio da integração de tecnologias inovadoras.
Uma Jornada de Veículos Aéreos Não Tripulados no Mundo da Cana-de-Açúcar
Keywords: Unmanned Aerial Vehicles; Sugarcane; Remote Sensing; Digital Agriculture; Machine Learning